Influence of temperature on electroreduction of anodically formed passive films on lead electrodes in H2SO4 Solutions : Part II: Electroreduction of PbO layers - Varela, Francisco Eduardo (1995)
Combined voltammetry and potentiostatic current transient techniques have been employed to study the electroreduction of anodically formed lead oxide layers, which build up beneath the initially grown PbSO4 crystal, on polycrystalline lead electrodes in concentrated sulphuric acid solution in the 0 to 50° C temperature range. Current transient analysis of the PbO electroreduction performed by using parametric identification procedures and nonlinear fit routines has demonstrated that kinetic data can be mainly interpreted in terms of a progressive nucleation and three-dimensional growth mechanism under charge transfer control, whereas in the initial short time range a process under H+ ion diffusion control has been detected. The phenomenological explanation of the temperature effect on electrode processes is based on the Arrhenius behaviour of kinetic operational parameters.